2018
DOI: 10.1016/j.tranpol.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

On sceptics and enthusiasts: What are the expectations towards self-driving cars?

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 14 publications
9
97
1
4
Order By: Relevance
“…AV's can be defined as those vehicles in which direct control by the driver is not required due to the self-driving characteristics of the vehicle [121]. In spite of the implications associated with potential increases in travel demand, especially from an environmental point of view, AV's technology offers the possibility to create a revolution in the transport system [122,123]. Potential advantages in this sense are those related to improvements in route operations, with consequent reductions in traffic congestion, fuel emission, cost and driving stress; improved road safety and the opportunity to engage with other activities while travelling.…”
Section: Discussion and Future Research Agendamentioning
confidence: 99%
“…AV's can be defined as those vehicles in which direct control by the driver is not required due to the self-driving characteristics of the vehicle [121]. In spite of the implications associated with potential increases in travel demand, especially from an environmental point of view, AV's technology offers the possibility to create a revolution in the transport system [122,123]. Potential advantages in this sense are those related to improvements in route operations, with consequent reductions in traffic congestion, fuel emission, cost and driving stress; improved road safety and the opportunity to engage with other activities while travelling.…”
Section: Discussion and Future Research Agendamentioning
confidence: 99%
“…Approximately 12% of participants would never accept self-driving cars on public roads, 14% would never ride in selfdriving cars, and 18% would never buy a self-driving car. These findings suggested that a nontrivial number of drivers will remain skeptical and apprehensive of self-driving vehicles, regardless of the level of safety attained by automation (also see Nielsen & Haustein, 2018;Piao et al, 2016;Schoettle & Sivak, 2014;Zmud, Sener, & Wagner, 2016). This possibility notwithstanding, perceived safety, although important, is not the only factor that will contribute to acceptance of high automation in vehicles.…”
Section: Limitations and Caveatsmentioning
confidence: 99%
“…Although fully self‐driving cars have yet to enter the consumer market, there is a growing body of research that attempts to understand the public's attitudes toward and likely acceptance of these vehicles. Studies have found that people's degree of acceptance varies by individual characteristics, with younger, male, or more tech savvy people generally more interested in using self‐driving cars than older, female, or less tech savvy people (Hohenberger, Spörrle, & Welpe, ; König & Neumayr, ; Lee et al., ; Nielsen & Haustein, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that although most people do not embrace the technology completely, they are not completely opposed to it. In particular, people anticipate that the technology could deliver benefits such as fewer crashes, reduced severity of crashes, lower vehicle emissions, better fuel economy, transportation solutions for older and disabled people, the possibility to engage in other activities while on the road, greater safety, and greater convenience (Howard & Dai, ; Hulse, Xie, & Galea, ; Nielsen & Haustein, ; Sanbonmatsu, Strayer, Yu, Biondi, & Cooper, ; Schoettle & Sivak, ).…”
Section: Introductionmentioning
confidence: 99%